Anglo-Saxon crops and weeds : a case study in quantitative archaeobotany - McKerracher, Mark James, 1986- (Access archaeology., 2019)
Farming practices underwent momentous transformations in the Mid Saxon period, between the 7th and 9th centuries AD. This study applies a standardised set of repeatable quantitative analyses to the charred remains of Anglo-Saxon crops and weeds, to shed light on crucial developments in crop husbandry between the 7th and 9th centuries.